RE-ORIENTANTION METHODS OF CORE SAMPLES: IMPLICATIONS TO SEDIMENT CORES FROM N. GREECE - Αηδονά Ε.; Κοντοπούλου Δ.; Scholger, R. (Bulletin of the Geological Society of Greece, 2004)
The different methods of re-orientation of core samples are discussed in the present study. In order to obtain results from core samples concerning the direction of the formation, their permeability and their anisotropy, it is essential first to bring all the pieces of the core into their initial position with regard to the North and to the horizontal (in-situ). In this study we emphasize particularly to the palaeomagnetic technique. This re-orientation method uses the magnetic components of the rocks (especially the viscous component) in order to determine the direction with regard to the North (declination). Also, the anisotropy method which helps us to correct the angle to the horizontal (inclination) is described here. Finally we applied the last two methods in non-oriented core samples from N. Greece and the significant importance of the re-orientation techniques to the palaeomagnetic studies is shown.